1 − 2 2 1 + 3 2 1 − 4 2 1 + 5 2 1 − ⋯ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Start with 1 + 2 2 1 + 3 2 1 + 4 2 1 + ⋯ = 6 π 2 .
Then if we divide both sides by 2 2 = 4 , then we find 2 2 1 + 4 2 1 + 6 2 1 + 8 2 1 + ⋯ = 2 4 π 2
Then, subtracting 2 × this infinite series from the first one, we have 1 − 2 2 1 + 3 2 1 − 4 2 1 + ⋯ = 6 π 2 − 2 ( 2 4 π 2 ) = 1 2 π 2 .